2008
DOI: 10.1016/j.neurobiolaging.2007.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced proteasome-dependent degradation of the CDK inhibitor p27kip1 in immortalized lymphocytes from Alzheimer's dementia patients

Abstract: Cyclin-dependent kinase inhibitor p27(kip1) (p27), a critical determinant for cell cycle progression, is an important regulation target of mitogenic signals. We have recently reported the existence of a molecular link between decreased p27 levels and enhanced phosphorylation of pRb protein and proliferation of immortalized lymphocytes from Alzheimer's disease (AD) patients. These cell cycle disturbances might be considered systemic manifestations, which mirror changes thought to occur in the brain, where post-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
64
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 44 publications
(71 citation statements)
references
References 52 publications
7
64
0
Order By: Relevance
“…Figure 1 shows a time course analysis of the effect of increasing doses of simvastatin on rates of proliferation, upon serum stimulation, of lymphoblasts from control and AD patients. In agreement with previous reports from this laboratory (de las Cuevas et al, 2003;Muñ oz et al, 2005Muñ oz et al, , 2007, the proliferative activity of AD lymphoblasts was significantly higher than that of control cells. Treatment of cells with simvastatin resulted in a significant inhibition of cell growth of both control and AD lymphoblasts in a dosedependent manner.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…Figure 1 shows a time course analysis of the effect of increasing doses of simvastatin on rates of proliferation, upon serum stimulation, of lymphoblasts from control and AD patients. In agreement with previous reports from this laboratory (de las Cuevas et al, 2003;Muñ oz et al, 2005Muñ oz et al, , 2007, the proliferative activity of AD lymphoblasts was significantly higher than that of control cells. Treatment of cells with simvastatin resulted in a significant inhibition of cell growth of both control and AD lymphoblasts in a dosedependent manner.…”
Section: Resultssupporting
confidence: 93%
“…pRb hyperphosphorylation releases E2F transcription factors, thus contributing to the expression of several growth and cell cycle regulatory genes with functional E2F binding sites in their promoters (Stevaux and Dyson, 2002). In agreement with previous reports (de las Cuevas et al, 2003;Muñ oz et al, 2005Muñ oz et al, , 2007 lymphoblasts from AD patients showed a higher degree of phosphorylation of pRb. The addition of SIM had no effect on the phosphorylation status of pRb in control cells, but it significantly reduced the levels of the hyperphosphorylated form of pRb in AD lymphoblasts.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Changes in CaM availability and/or in the intrinsic functional properties of the molecule were linked to disruption of Ca 2+ homeostasis in immortalized lymphocytes from late-onset AD patients [14]. Interestingly, the distinct Ca 2+ response of AD was associated with enhanced cell proliferation compared to control lymphoblasts from age-matched individuals [16,17]. These features were considered as peripheral signs of the disease, as current evidence relates the process of neuronal apoptosis occurring in AD to the aberrant reentry of differentiated neurons into the cell cycle [18][19][20].…”
Section: Introductionmentioning
confidence: 99%